Association of primary sclerosing cholangitis with HLA-B8. Issue 1 (January 1983) - Chapman, R W; Varghese, Z; Gaul, R; Patel, G; Kokinon, N; Sherlock, S
Abstract : The frequency of HLA antigens was studied in 25 patients with primary sclerosing cholangitis and compared with a control group of 562 kidney donors. Fourteen patients also had ulcerative colitis. A significant increase in the frequency of HLA-B8 (60%) was found in the primary sclerosing cholangitis patients compared with controls (25%) (p less than 0.001). HLA-B8 was found in eight patients with ulcerative colitis. The frequency of HLA-B12 was significantly decreased (8%) compared with controls (30%) (p less than 0.02). Piecemeal necrosis was observed on liver histology in 66% of HLA-B8 positive and 50% of HLA-B8 negative patients. Low titres of serum autoantibodies were frequently found in the primary sclerosing cholangitis group but did not correspond to the presence of HLA-B8. Raised serum concentrations of IgM and IgG were not related to HLA-B8. This study has shown that in patients with primary sclerosing cholangitis there exists a disease susceptibility gene closely associated with the B locus of the major histocompatibility complex which may be modified by other factors such as ulcerative colitis. Patients with ulcerative colitis and HLA-B8 may be particularly liable to develop primary sclerosing cholangitis.